2020
DOI: 10.3390/su12124981
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Productivity Growth and Its Determinants in South and Southeast Asian Countries

Abstract: Improving agricultural productivity is a priority concern in promoting the sustainable development of agriculture in developing countries. In this study, we first apply stochastic frontier analysis (SFA) to analyze the growth of agricultural total factor productivity (TFP) and its three components (technical change—TC, technical efficiency change—TEC and scale change—SC) in 15 south and southeast Asian countries covering the period 2002 to 2016. Then, the determinants of agricultural TFP growth are identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 53 publications
2
39
0
Order By: Relevance
“…The possible reason for this long-run relationship between institutional performance and N 2 O emissions is that N 2 O emissions are primarily produced from agricultural activities (use of nitrogen-fertilizers, waterlogging and croptillage, etc.) [54] and South Asian countries are under-developed, having a large share of the agriculture sector that makes a significant contribution in economic activities of these countries [88]. In the development process, an increase in institutional performance (stability of government, control on corruption, a better situation of law and order, and improved socioeconomic conditions) leads to enhance agricultural activities, which causes an increase in N 2 O emissions.…”
Section: Slope Homogeneity Testmentioning
confidence: 99%
“…The possible reason for this long-run relationship between institutional performance and N 2 O emissions is that N 2 O emissions are primarily produced from agricultural activities (use of nitrogen-fertilizers, waterlogging and croptillage, etc.) [54] and South Asian countries are under-developed, having a large share of the agriculture sector that makes a significant contribution in economic activities of these countries [88]. In the development process, an increase in institutional performance (stability of government, control on corruption, a better situation of law and order, and improved socioeconomic conditions) leads to enhance agricultural activities, which causes an increase in N 2 O emissions.…”
Section: Slope Homogeneity Testmentioning
confidence: 99%
“…Ref. [18] applied Stochastic Frontier Analysis (SFA) to analyze the growth of agricultural total factor productivity (TFP) in 15 south and southeast Asian countries, over the period 2002-2016. The results revealed that the sample countries witnessed an overall decline in agricultural productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Over timeshare of the Agriculture sector in GDP and employment has declined. As in 2003, Agriculture's share in south Asian GDP decreased from 23% in 2000 to 19% in 2017 Moreover, during the last two decades, the average growth rate of agriculture is 3.2% for South Asian countries (Liu et al, 2020). Nevertheless, the fall in agriculture growth rate does not imply a decline in overall agriculture productivity.…”
Section: Research Articlementioning
confidence: 99%